Retrospective review of paediatric rheumatic mitral valve repairs and replacements done at Red Cross War Memorial Children's Hospital (RCWMCH) over a decade - Mureko, Alfred (Division of Cardiology, 2017)
Objectives: Rheumatic heart disease remains a significant cause of morbidity and mortality and it is the leading cause of acquired paediatric cardiac disease in the developing world. The aim of this study was to understand the burden of rheumatic heart disease and to review the surgical management of rheumatic mitral valve disease at our institution. Methods: We retrospectively reviewed 76 consecutive patients who underwent mitral valve surgery for rheumatic heart disease between 1998 and 2010. The results and follow-up were reviewed, where death and reoperation were the primary endpoints. The follow up included a review of the latest information from the patients' medical records and telephonic interviews or home visits. Results: A 91% follow up was achieved over a median follow up period of 7.4 years (range 0.1-15.2 years). The mean age at surgery was 10.7 years (SD +- 2.7 years). The females constituted 66% and males 34%. Mitral valve repairs were performed in 64% of patients and of the 64% repairs, 0.06% only had commissurotomies. Replacements were performed in 36% of patients. All mitral valve replacements were mechanical prostheses. The actuarial freedom from reoperation for repairs was 83% (+-2.2) and 66% (+-3.4) at 5 and 10 years and for replacements was 87% (+-4.8) and 87%(+-4.8) respectively (p=0.27). Actuarial freedom from embolic cerebrovascular accidents in the repair group at both 5 and 10 years was 100%, compared to 90.2% (+-6.6) and 79% (+-12.0) for the replacement group at 5 and 10 years respectively (p=0.02). Actuarial freedom from death at 5 and 10 years for children over 12.8 years was 77.7% (+-9.9) and 69.1% (+-12.0) respectively, compared to 93.6% (+-3.6) and 93.6% (+-3.6) for children under 12.8 years (p=0.03). No statistical significant difference was noted in freedom from valve related failure and death between repairs and replacements. Conclusions: There was no significant difference in survival between mitral valve repairs and replacements. There was surprisingly worse survival among children who were above 12.8 years at time of the surgery.